2013
DOI: 10.1002/cctc.201200492
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Efficient Pt–Re/TiO2 catalysts for Water‐Gas‐Shift: On the Effect of Rhenium

Abstract: The catalytic performance of Pt–Re/TiO2 catalysts, that is, activity and stability, in single‐stage water gas shift reactions was investigated by studying the influence of preparation strategies, Pt/Re molar ratios, and metals contents. Results show that sequential impregnation of Re precursor prior to Pt precursor without intermediate pretreatment is the optimum preparation strategy. The Pt/Re ratio of unity with 0.5 wt. % Pt content resulted in the most significant effect on activity and stability. In situ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…This synergy allows for higher turnover of glycerol (or CO for WGS). This is also in agreement with previous reports that Re in an oxidized state (e.g., ReO x ) could provide sites for CO oxidation [32] and water activation [19].…”
Section: Fig 7 Raman Spectra Of Ptre/c Catalyst With Different Treatsupporting
confidence: 93%
See 1 more Smart Citation
“…This synergy allows for higher turnover of glycerol (or CO for WGS). This is also in agreement with previous reports that Re in an oxidized state (e.g., ReO x ) could provide sites for CO oxidation [32] and water activation [19].…”
Section: Fig 7 Raman Spectra Of Ptre/c Catalyst With Different Treatsupporting
confidence: 93%
“…ReO x was also proposed to be present as a redox center to enhance the WGS activity, in which ReO x could be reduced by CO (generating CO 2 ) and re-oxidized by H 2 O (forming H 2 ) [19]. We recently studied the catalytic performances of activated carbon-supported Pt and Pt-Re catalysts for glycerol aqueous-phase reforming (APR) [5,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have indicated that the presence of Re has a beneficial role in the activity of Pt‐based catalysts in the LT‐WGS reaction 17. Although only a few experimental studies have been performed to understand the role of Re, they agree that Re provides an additional reaction pathway to activate H 2 O 17a. e, h In these studies, however, Pt and Re atoms are supported on titania and zirconia, which are promoters for Pt‐catalyzed LT‐WGS reactions themselves, and therefore their presence might obscure the isolation of the Re effect on the WGS reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies have also demonstrated that Pt-Re/TiO 2 has greater activity for the WGS reaction compared to Pt/TiO 2 due to dissociation of water on ReO x . [26][27][28][29][30] Furthermore, density functional theory (DFT) calculations for the WGS reaction on Pt 3 Re(111) report that the active Pt-Re site is likely to contain partially oxidized ensembles. 31 It has also been proposed that Re-OH formation promotes hydrogenolysis of glycerol through direct activation of C-OH bonds.…”
mentioning
confidence: 99%